Analysis of Factors that Increase Customer Satisfaction Coffee Products - Suryawardana, Edy; Nurdeagraha, Doni (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2020)
Satisfaction is the level of feeling where someone states the comparison of the product's performance (service) received and expected. This study aimed to determine the effect of price, service quality, product quality, product diversity, promotion, and location on customer satisfaction. This study uses a quantitative approach. The sample is the consumer